“The Fate of Daniel Gwinn” : A Narrative Obituary Poem - Caplan, Ronald (Ethnologies, 1991)
This paper discusses one narrative obituary verse, ‘‘The Fate of Daniel Gwinn”, found in the Aspy Bay Region of Cape Breton Island, Nova Scotia. It is argued that the poet, Andrew Dunphy, attempted to play a role in preservation of the local community by giving a particular version of the events surrounding the death, trying thereby to ease troubled minds. The work of this narrative obituary verse, then, goes beyond religious reassurance. While a private event — narrative obituary poems in this community were usually given only to the immediate family; “The Fate of Daniel Gwinn”, for instance, was performed as part of the family’s Sabbath Day readings — but this poem also “got out”, as they say, becoming part of the local song repertoire.